Utilization of Smoked Fish Processing Waste in Bulak Fish Center Surabaya as Fish Feed Raw Material - Mohamad Mirwan; Firra Rosariawari; Syahrul Munir (Nusantara Science and Technology Proceedings, 2021)
Fish processing waste management in the coastal area of ??Kenjeran Beach is very critical to the environment. The production process of smoked fish has also created various solid wastes in the form of offal, head, tail, and fish fins. In this case, the solid wastes produced were disposed of without any prior management thus it can cause environmental pollution to reduce the pollution, it is necessary to utilize it to minimize the pollution. Bulak Fish Center Surabaya has plenty of smoked fish retailers selling their catches. Waste management has not been carried out optimally because it was relatively expensive for retail scale traders, so there needs to be an alternative utilization of fish waste. Wastes generated from smoked fish have great potential to be used as raw material for fish feeds with a fairly high content of protein and lipids. In addition to protein and amino acid sources, fish waste also contains minerals and vitamins. Utilization of smoked fish waste such as innards in the form of digestive organs, heads, and tails of these fish can be used as fish pellets raw material. The knowledge about waste and how to utilize the waste as fish feed needs to be informed to the fish processing business owners and the community around the Bulak Fish Center Surabaya. This community service will provide basic knowledge, and counseling, and become a pioneer of fish feed production so that it can be applied as fish feed materials used for fish cultivation.